Endogenous testosterone level and testosterone supplementation therapy in chronic obstructive pulmonary disease (COPD): a systematic review and meta-analysis. Issue 8 (13th August 2013) - Atlantis, Evan; Fahey, Paul; Cochrane, Belinda; Wittert, Gary; Smith, Sheree
Abstract : Objective: Low testosterone level may be a reversible risk factor for functional disability and deterioration in patients with chronic obstructive pulmonary disease (COPD). We sought to systematically assess the endogenous testosterone levels and effect of testosterone therapy on exercise capacity and health-related quality of life (HRQoL) outcomes in COPD patients, as well as to inform guidelines and practice. Design: Systematic review and meta-analysis. Data sources: We searched PubMed, Scopus, Cochrane Library, CINAHL, Health Source Nursing and PsychINFO and the reference lists of retrieved articles published before May 2012. Inclusion criteria: Observational studies on endogenous testosterone levels in people with chronic lung disease compared with controls, or randomised controlled trials (RCTs) on testosterone therapy for exercise capacity and/or HRQoL outcomes in COPD patients were eligible. Data extraction and analysis: Data on the mean difference in endogenous total testosterone (TT) values, and the mean difference in exercise capacity and HRQoL values were extracted and pooled using random effects meta-analysis. Results: Nine observational studies in 2918 men with COPD reported consistently lower levels of TT compared with controls (weighted mean difference was –3.21 nmol/L (95% CI −5.18 to −1.23)). Six RCTs in 287 participants yielded five studies on peak muscle strength and peak cardiorespiratory fitness outcomes (peak oxygen uptake (VO2 ) and workload) and three studies on HRQoL outcomes. Testosterone therapies significantly improved peak muscle strength (standardised mean difference (SMD) was 0.31 (95% CI 0.05 to 0.56)) and peak workload (SMD was 0.27 (95% CI 0.01 to 0.52)) compared with control conditions (all but one used placebo), but not peak VO2 (SMD was 0.21 (95% CI −0.15 to 0.56)) or HRQoL (SMD was –0.03 (95% CI −0.32 to 0.25)). Conclusions: Men with COPD have clinically relevant lower than normal TT levels. Insufficient evidence from short-term studies in predominately male COPD patients suggests that testosterone therapy improves exercise capacity outcomes, namely peak muscle strength and peak workload.